Stress, Anguish, Anxiety and Resilience of University Teachers in the Face of Covid-19 - CASIMIRO URCOS, Walther Hernán; CASIMIRO URCOS, Consuelo Nora; BARBACHÁN RUALES, Enrique Alejandro; CASIMIRO URCOS, Javier Francisco (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTSocial isolation, which is a measure imposed due to the consequences of the Covid-19 pandemic, it significantly affects people's mental health. The objective was to determine the emotional states of university teachers in the face of Covid-19. Stress showed a high level of 89.4%; anxiety, with a high level of 94.2%; anxiety with a high level of 92.3%. Regarding resilience, this was manifested at a medium-high level with 60.9% of those surveyed. In conclusion, the emotional state of most of the teachers is low and their response through their resilience is medium-high.RESUMENEl aislamiento social, que es una medida impuesta debido a las consecuencias de la pandemia del Covid-19, afecta de un modo considerable la salud mental de las personas. El objetivo fue determinar los estados emocionales de los docentes universitarios frente al Covid-19. El estrés manifestó un nivel alto en el 89,4%; la angustia, con un nivel alto del 94,2%; la ansiedad con un nivel alto del 92,3%. Respecto a la resiliencia, esta se manifestó en un nivel medio-alto con un 60,9% de los encuestados. Se concluye que el estado emocional de la mayoría de los docentes es bajo y su respuesta a través de su resiliencia es medio-alto.